Effects of different Nitrogen rates on hay yield and some quality traits of Sudan grass and sorghum x Sudan grass hybrid varieties - Gulumser D.D.; Mut H. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
This research was conducted to determine the effects of six nitrogen rates (0, 40, 80, 120, 160, 200 kg ha-1) on the hay yield and some quality characteristics of Sudan grass and sorghum x Sudan grass hybrid grown in Yozgat ecological conditions in 2013-2014. As plant material, one Sudan grass and two sorghum x Sudan grass hybrids varieties were used. The experiment was arranged in split plot design with three replications. The average plant height, leaf ratio, hay yield, crude protein ratio, crude protein yield, ADF and NDF ratio were ranged from 200.9 – 205.5 cm, 36.02 – 39.90 %, 1.39 – 2.55 t/da, 8.17 – 11.90 %, 113.5 – 304.9 kg/ha, 37.51 – 40.31 % and 62.59 – 67.34 % in the 2013-2014 respectively. In this study P, K, Ca and Mg content of the varieties were found sufficient in both years. At the end of the two years study, in terms of hay and crude protein yield, Aneto and Bovital varieties which are sorgum x Sudan grass hybrids were superior with 80 kg ha-1 N rates under irrigated conditions.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)